2008
DOI: 10.3748/wjg.14.1346
|View full text |Cite
|
Sign up to set email alerts
|

COOH-terminal deletion of HBx gene is a frequent event in HBV-associated hepatocellular carcinoma

Abstract: AIM:To investigate the hepatitis B virus (HBV) x gene (HBx) state in the tissues of HBV-related hepatocellular carcinoma (HCC) in Chinese patients and whether there were particular HBx mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 23 publications
3
33
1
Order By: Relevance
“…Therefore, COOH-terminal deletion is a major feature of HBx identified in tumor tissue. In addition, a specific integration of HBx at GA-rich region of 17p13 locus (repeat region 56047...56210/ rpt_family = 'GA-rich') was also found in 6 of the 14 HCC patients in our previous study (24).…”
Section: Hbx Gene Sequencing In Hepatocellular Carcinoma Tissues Fromsupporting
confidence: 54%
See 1 more Smart Citation
“…Therefore, COOH-terminal deletion is a major feature of HBx identified in tumor tissue. In addition, a specific integration of HBx at GA-rich region of 17p13 locus (repeat region 56047...56210/ rpt_family = 'GA-rich') was also found in 6 of the 14 HCC patients in our previous study (24).…”
Section: Hbx Gene Sequencing In Hepatocellular Carcinoma Tissues Fromsupporting
confidence: 54%
“…HBx also plays a role in regulating a series of cell-signaling cascades, most notably in the Ras-and Raf-induced mitogen-activated protein kinase pathways, and in inactivation of tumor suppressive genes through promoter hypermethylation (30). Previous studies have demonstrated that HBx deletion, especially the COOHterminal deletion of HBx, is a frequent event in HBV-associated HCC tissues (11,12,24).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that a frequently occurring HBx mutation is the deletion of the COOH-terminus in tissue samples of patients with HCC [3][4][5] . These data suggest that COOH-terminal truncations of HBx may play a critical role in hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…As such, HBx is involved in the regulation of genotoxic stress responses, protein degradation pathways, cell proliferation and apoptosis, immune responses and cell adhesion [2] . It has been reported that COOH-terminal deletions of HBx are frequent events in HBV-associated HCC tissues [3][4][5] . In addition, our previous study found a natural mutant of HBx that had 27 truncated amino acids at the COOH-terminal (termed HBxΔ127) [6] , which was consistent with other reports [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation